2004
DOI: 10.1172/jci21647
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of 11β-hydroxysteroid dehydrogenase type 2 expression

Abstract: The enzyme 11β-hydroxysteroid dehydrogenase type 2 (11βHSD2) is selectively expressed in aldosterone target tissues, where it confers aldosterone selectivity for the mineralocorticoid receptor by inactivating 11β-hydroxyglucocorticoids. Variable activity of 11βHSD2 is relevant for blood pressure control and hypertension. The present investigation aimed to elucidate whether an epigenetic mechanism, DNA methylation, accounts for the rigorous control of expression of the gene encoding 11βHSD2, HSD11B2. CpG island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
141
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(148 citation statements)
references
References 42 publications
(20 reference statements)
5
141
2
Order By: Relevance
“…Thus, time-course studies after UNX in the remaining kidney must be performed in order to identify relevant regulatory factors for the expression of 11b-HSD1 and 11b-HSD2. A number of factors regulating the expression of 11b-HSD enzymes have previously been identified including TNF-a, Erg1, NF-kB, NF1, C/EBPs, GR, Sp1/Sp3, Arnt, PPAR-a/PPAR-g, IL1, glucocorticoids, sex steroids, and thyroid hormones (Alikhani-Koopaei et al 2004, Tomlinson et al 2004, Kostadinova et al 2005, Alikhani-Koupaei et al 2007, Wake et al 2007, Ignatova et al 2009). The ultimate proof for a pivotal relevance of one or a combination of these factors would require the investigation of animals with specific over-or under-expression in the cortical collecting duct.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, time-course studies after UNX in the remaining kidney must be performed in order to identify relevant regulatory factors for the expression of 11b-HSD1 and 11b-HSD2. A number of factors regulating the expression of 11b-HSD enzymes have previously been identified including TNF-a, Erg1, NF-kB, NF1, C/EBPs, GR, Sp1/Sp3, Arnt, PPAR-a/PPAR-g, IL1, glucocorticoids, sex steroids, and thyroid hormones (Alikhani-Koopaei et al 2004, Tomlinson et al 2004, Kostadinova et al 2005, Alikhani-Koupaei et al 2007, Wake et al 2007, Ignatova et al 2009). The ultimate proof for a pivotal relevance of one or a combination of these factors would require the investigation of animals with specific over-or under-expression in the cortical collecting duct.…”
Section: Discussionmentioning
confidence: 99%
“…46 Interestingly, hypermethylation of HSD11B2 CpG islands correlates with lower levels of HSD11B2 expression. 45 Low methylation levels of HSD11B2 were observed in the placenta (were HSD11B2 expression is high), whereas in skeletal muscle (low HSD11B2 expression) the HSD11B2 promoter was hypermethylated. 45 Furthermore, it has been shown that the activity of the HSD11B2 promoter is directly regulated by methylation.…”
Section: Epigenetic Regulation Of Hsd11b2 Expressionmentioning
confidence: 97%
“…45 Low methylation levels of HSD11B2 were observed in the placenta (were HSD11B2 expression is high), whereas in skeletal muscle (low HSD11B2 expression) the HSD11B2 promoter was hypermethylated. 45 Furthermore, it has been shown that the activity of the HSD11B2 promoter is directly regulated by methylation. 45 These data show that exposures that change HSD11B2 methylation status in the placenta can result in transcriptional repression of the gene, causing the fetus to be exposed to higher levels of cortisol that may adversely affect fetal development.…”
Section: Epigenetic Regulation Of Hsd11b2 Expressionmentioning
confidence: 97%
See 2 more Smart Citations